Electrically conductive palm oil-based coating with UV curing ability - Ramlan, S.N.A.; Basirun, Wan Jefrey; Phang, S.W.; Ang, D.T.C. (Elsevier, 2017)
Environmentally friendly products are gaining popularity recently, in line with the increasing global demands for green technology. UV-curable coating is one of them since it involves minimal, if any, emission of volatile organic compounds during the curing process. Besides, UV curing technology enables coatings to be cured within a much shorter time compared to the thermal curing process. The aim of this study is to produce an electrically conductive UV-curable coating which is environmentally friendly. Polyaniline is a polymer with excellent electrical conductivity and known to exhibit anti-corrosion properties through passivation. However, polyaniline itself is not a good coating binder, as it tends to produce a brittle film with poor adhesion properties. Therefore, in this work, palm oil-based polyester binder was synthesized and blended with polyaniline to produce an electrically active coating with improved film adhesion properties. The alkyd resin was formulated with a considerable amount of maleic acid formulation in order to render it UV curable. Both alkyd and polyaniline were characterized using FTIR, 1H NMR, TGA, and UV-Vis. Some of the tests carried out to investigate the film properties of the coatings included the pencil hardness test, adhesion tape test, water and chemical resistant test, conductivity, and thermal stability. In addition, corrosion studies of the coatings on mild steels were determined using open circuit potential (OCP) values, Tafel analysis and electrochemical impedance spectroscopy (EIS).